Subantimicrobial Dose Doxycycline Worsens Chronic Arthritis-Induced Bone Microarchitectural Alterations in a Mouse Model: Role of Matrix Metalloproteinases? - Horváth, Ádám; Botz, Bálint; Kiss, Tamás; Csekő, Kata; Kiss, Ibolya; Felinger, Attila; Szabados, Tamara; Kenyeres, Éva; Bencsik, Péter; Mócsai, Attila; Ferdinandy, Péter; Helyes, Zsuzsanna (Frontiers in Pharmacology, 2019)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease hallmarked by irreversible damage of cartilage and bone. Matrix metalloproteinases (MMPs) involved in connective tissue remodeling play an important role in this process. Numerous MMPs have been examined in humans and animals, but their functions are still not fully understood. Therefore, we investigated the role of MMPs in the K/BxN serum-transfer model of rheumatoid arthritis with the broad-spectrum MMP inhibitor subantimicrobial dose doxycycline (SDD) using complex in vivo and in vitro methodolgy. Methods: Chronic arthritis was induced by repetitive i.p. injections of K/BxN serum in C57BL/6J mice. SDD was administered daily in acidified drinking water (0.5 mg/ml, 80 mg/kg) during the 30-day experimental period. Mechanonociceptive threshold of the paw was evaluated by aesthesiometry, grasping ability by grid test, arthritis severity by scoring, neutrophil myeloperoxidase activity by luminescence, vascular hyperpermeability and MMP activity by fluorescence in vivo imaging and the latter also by gelatin zymography, bone structure by micro-computed tomography. Plasma concentrations of doxycycline were determined by liquid chromatography-mass spectrometry analysis. Results: K/BxN serum induced significant mechanical hyperalgesia, joint function impairment, increased myeloperoxidase activity and vascular hyperpermeability. Significant increase of MMP activity was also observed both in vivo and ex vivo with elevation of the 57, 75 and 92 kDa gelatinolytic isoforms in the arthritic ankle joints, but neither MMP activity nor any above described functional parameters were influenced by SDD. In contrast, increased early and decreased late edema formation was observed after SDD administration. Most importantly, SDD significantly reduced bone mineral density in the distal tibia and enhanced percent increase of open pore volume and the Euler number in the ankle. Arthritis-induced microarchitectural alterations demonstrating increased irregularity and cancellous bone remodeling, such as increased Euler number was significantly elevated by SDD in both regions. Conclusions: We showed increase of various MMP activities in the joints by in vivo fluorescence imaging together ex vivo zymography, and investigated their functional significance using the broad-spectrum MMP inhibitor SDD in the translational RA model. This is the first demonstration that SDD alters arthritis-induced bone microarchitecture, but it appears to be independent of MMP inhibition.